Modification mechanism of combined nanomaterials on high performance concrete and optimization of nanomaterial content. (1st April 2023) - Du, Xiaoqi; Li, Yanlong; Huangfu, Binghui; Si, Zheng; Huang, Lingzhi; Wen, Lifeng; Ke, Meiwei
Abstract: With the increasing quality of concrete construction, the requirements for concrete performance have also gradually increased. In this paper, the effect of nanomaterials on concrete performance was investigated by incorporating nanomaterials (nano-SiO2 and nano-Fe2 O3 ) into concrete to prepare high performance concrete (HPC). The optimum content of nanomaterials was determined by response surface method (RSM), which revealed the influence mechanism of nanomaterial on concrete performance. Results showed that adding nanomaterials remarkably enhanced the mechanical properties of concrete. When the dosage of nano-SiO2 was 3.54% and the dosage of nano-Fe2 O3 was 4.24%, which was the optimum dosage of nanomaterials. Concrete with this dosage had compressive, splitting tensile, and flexural strength of 67.27 MPa, 8.95 MPa, and 9.56 MPa, respectively. The two types of nanomaterials can achieve excellent coupling effect. Nano-SiO2 acted as an auxiliary cementing material, and nano-Fe2 O3 accelerated the hydration reaction rate of cementing materials. According to the microstructure of nanoconcrete, energy dispersive spectrometer (EDS) elemental analysis and thermogravimetry analysis (TGA), it was concluded that the incorporation of nanomaterials cannot produce new kinds of hydration products in concrete but can produce more hydration products. These results can serve as theoretical reference for HPC preparation. Highlights: The incorporated nano-SiO2 and nano-Fe2 O3 can achieve excellent coupling effect in improving the performance of concrete. The optimal content of the combined nanomaterials was determined based on experiments and response surface method. Incorporating nanomaterials cannot produce new kinds of hydration products, but can produce more hydration products.